Landasan Sosiokultural dalam Pengembangan Kurikulum PAI pada Mata Pelajaran Al-Qur'an Hadits MTs: Sociocultural Foundations in the Development of Islamic Education Curriculum for the Qur'an and Hadith Subject at Islamic Junior High Schools (MTs) - Afifah, Nurul; Marwiji, Muh. Hasan (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
The rapid pace of social and cultural change demands that Islamic Religious Education (PAI) curricula be more adaptive to students’ local contexts. This study aims to analyze the sociocultural foundation in developing the Al-Qur'an Hadith curriculum at Madrasah Tsanawiyah (MTs). Employing a qualitative approach through a structured literature review, data were sourced from relevant primary and secondary references published within the last five years. Designed to explore the conceptual framework for integrating sociocultural values into PAI curriculum development, the study reveals that strengthening local values—such as tolerance, respect for traditions, and positive social character building—constitutes a crucial component of Al-Qur'an Hadith learning. A curriculum rooted in sociocultural values not only enhances the relevance of educational content to students’ daily lives but also promotes contextual internalization of Islamic teachings. These findings imply the need for a more reflective curriculum approach that aligns with societal dynamics and serve as a conceptual basis for developing responsive and transformative Islamic education curricula in madrasahs.